2019
DOI: 10.1051/0004-6361/201833282
|View full text |Cite
|
Sign up to set email alerts
|

Telluric correction in the near-infrared: Standard star or synthetic transmission?

Abstract: Context. The atmospheric absorption of the Earth is an important limiting factor for ground-based spectroscopic observations and the near-infrared and infrared regions are the most affected. Several software packages that produce a synthetic atmospheric transmission spectrum have been developed to correct for the telluric absorption; these are Molecfit, TelFit, and Transmissions Atmosphériques Personnalisées pour l'AStronomie (TAPAS). Aims. Our goal is to compare the correction achieved using these three tellu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
2
18
1
Order By: Relevance
“…The fit's residuals deviate from unity by 1.0% on average, comparable to the unaffected regions of the spectrum and the performance of radiative transfer codes. (Ulmer-Moll, S. et al 2019). One potential flaw in our model is that modelling all points without significant telluric signal as unity creates discontinuities in the telluric wings, however, Figure 6 (bottom) indicates these discontinuities are small, and most users will prefer to mask affected pixels rather than dividing out.…”
Section: Model Goodness Of Fitmentioning
confidence: 99%
“…The fit's residuals deviate from unity by 1.0% on average, comparable to the unaffected regions of the spectrum and the performance of radiative transfer codes. (Ulmer-Moll, S. et al 2019). One potential flaw in our model is that modelling all points without significant telluric signal as unity creates discontinuities in the telluric wings, however, Figure 6 (bottom) indicates these discontinuities are small, and most users will prefer to mask affected pixels rather than dividing out.…”
Section: Model Goodness Of Fitmentioning
confidence: 99%
“…On a final note, the method described here will certainly fail in the infrared where the lines density of water is too high. A possible solution would be to perform a first order correction by telluric lines modelling (Seifahrt et al 2010;Ulmer-Moll et al 2019) before applying the PCA as a second-stage correction on the residuals.…”
Section: Telluric Line Correctionmentioning
confidence: 99%
“…A.1. Recent work by Ulmer-Moll et al (2019) demonstrated that MOLECFIT is an excellent tool for removing telluric lines from CRIRES spectra and that it performs better than the classical approach of using a telluric standard star. In our correction, each of the CRIRES detectors was treated independently.…”
Section: Observations and Data Reductionmentioning
confidence: 99%